The paradox of technical governance: A public opinion survey's political process and its results. (January 2020) - Peng, Yaping
The logic of technical governance goes as follows: the knowledge of society can be obtained by the state via technology, and thus social problems are identified and solutions are found. Questions have been raised about whether technical governance would ever work. For many the answer is negative and doubtful. However, one defense remains: technical governance fails not because the idea is inherently flawed but because the technology is not good. Would technical governance succeed with better methodology and more technical rigor? In order to challenge this defense, this paper examines the operation of opinion polls—a form of technical governance supported by rigorous quantitative social research methodology—run by a sub-district government in the city 'S'. In particular, this paper asks whether it is possible for a government-run poll to reflect manipulated public opinion, despite the strictest compliance with quantitative polling methodology. The finding of this paper gives an affirmative answer. It argues that on the surface, polls are statistical surveys, but in actuality they are a political process controlled by the government despite their compliance with all statistical requirements. The power structure of the local government determines the questionnaire items, their multiple-choice answers (the screening, compressing, and quantifying of social scenarios), and the final make-up of the public opinion index. The rigorousness of methodology does not guarantee the authenticity of 'public opinion' in final poll figures. More likely, the outcome is controlled by those who organize polls. Hence, quantifiable technical governance presents a contradiction: the state manufactures biased public opinions precisely when it is looking for unbiased public opinions. In the end, the government constructs an image of society that is its own reflection.